A cross-linguistic study of motion event acquisition in Japanese and Chinese: through the lens of figure and ground components - Xu Zhaorong,; Roslina Mamat,; Zaid Mohd Zin, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Numerous cross-linguistic studies on motion events have been undertaken to test the thinking-for speaking hypothesis, with a remarkable lead over the Path and Manner components. Yet, unexpectedly, the core entities in motion events such as Figure and Ground have garnered relatively limited focus. The current study shifts the focus to examine the way how subjects encode the Figure and Ground information through a narrative task, involving Chinese learners who learn Japanese as their foreign language (JFL), Chinese native speakers, and Japanese native speakers. The results revealed that the typological framework is too narrow to explain observed linguistic variations in the acquisition process. The striking differences followed from syntactic structure variations in the utterances of how Japanese versus Chinese encode the Figure and Ground information, which suggest the joint impact of typological and syntactic factors on language acquisition. In addition, it is clearly shown that the JFL learners patterned to a large degree with the Japanese native speakers rather than the Chinese native speakers concerning the distribution of Figure and Ground information by motion event type. This means that to some extent the JFL learners have acquired the target-like way to report Figure and Ground information in the narrative task, showing a limited role of the L1 thinking for speaking patterns.